Asian elephants' social structure and mineral lick usage in a Malaysian rainforest using camera traps - Hii, Ning (2017)
Elephants (Family Elephantidae) are animals that rely on complex social behavior and organization for survival. The current literature on elephant social organization come from studies in African savannas, an open environment where animals are relatively easy to observe and study. Much less is known, however, about the social behavior of forest elephants, particularly of wild elephants (Elephas maximus) in Southeast Asia. Wild elephants in Malaysian rainforests regularly visit mineral licks to supplement their diet with nutrients and to acquire clay to buffer secondary plant compounds This provides a great opportunity to set up camera traps and regularly observe animals that otherwise would be impossible to study in their natural environment. Thus, the objective of this study is 1) to assess the feasibility of using camera traps to study the social structure of elephants in the wild; 2) to describe their social structure; and 3) to quantify wild Asian elephant patterns of mineral lick usage. Individuals were identified using features on the ears, body and tail, or any other prominent profile; and associations between elephants were recorded. Camera traps were set up at a Sira in the Belum Temenggor Forest Complex from October 2012 till October 2013. Video data were retrieved monthly. In total, we recorded 951 hours of videos representing 165 elephant visits. We were able to identify 55 adult individuals while 21 offspring in the age classes of newborn, infants, and juveniles were unidentified over the course of the study. The identified individuals included 26 female adults, 8 female subadults, 15 male adults and 6 male subadults. Seven female family units and four mother-calf units were identified with a median group size of 6 and 2 individuals, respectively. The results show that forest Asian elephants live in smaller groups than their African savanna counterparts. Among the identified elephants, resident family groups were regularly detected, suggesting that mineral licks are important for the feeding ecology of elephants though the reason is still unclear. This study thus provides a baseline of Asian elephant social structure and mineral lick use in Peninsular Malaysia using camera trapping as a recording technique.